2016
DOI: 10.14306/renhyd.20.3.237
|View full text |Cite
|
Sign up to set email alerts
|

Hábitos alimentarios y actividad física en relación con el sobrepeso y la obesidad en España

Abstract: Introducción: El objetivo del presente estudio es analizar los hábitos de alimentación y ejercicio físico de la población española en el año 2012 y su relación con el sobrepeso y la obesidad. Material y Métodos: Estudio transversal de la Encuesta Nacional de Salud de España del año 2012. Se realizó un análisis descriptivo de los hábitos alimentarios y actividad física en la población general y por sexos con edades comprendidas entre los 18 y los 90 años y un análisis de regresión logística multinomial calculan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
4
0
3
Order By: Relevance
“…In comparison to the patients with obesity, the Pardo questionnaire results showed that patients with obesity were less compliant with the basic features of a healthy diet. The WHO has published recommendations on the components of a healthy diet [ 19 ], although the relationship of certain food groups with overweight and obesity continues to be under debate [ 20 , 21 , 22 , 23 ]. The groups did not differ in their alcohol consumption, which was found to be higher in people with obesity versus overweight in a study in the USA [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to the patients with obesity, the Pardo questionnaire results showed that patients with obesity were less compliant with the basic features of a healthy diet. The WHO has published recommendations on the components of a healthy diet [ 19 ], although the relationship of certain food groups with overweight and obesity continues to be under debate [ 20 , 21 , 22 , 23 ]. The groups did not differ in their alcohol consumption, which was found to be higher in people with obesity versus overweight in a study in the USA [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no between-group difference in IPAQ score, which may be explained by the large percentage of patients aged over 70 years, given that this questionnaire is more appropriate for individuals below this age. The practice of physical activity several times a week has been related to weight loss [ 21 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 30 years, it has multiplied by 2.3. Men show greater obesity and being overweight than women [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity does not fully obey a linear and quantitative relationship between ingested and spent calories. Frequent physical activity—more than 2 times per week—is associated with a reduction in excess weight [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Según la Organización Mundial de la Salud (OMS) en el año 2016 el 13% de la población adulta mundial (un 11% de los hombres y un 15% de las mujeres) eran obesos 3 . En Europa la prevalencia de la obesidad ha aumenta-do considerablemente 9 . Se estima que algunos países europeos, como España, el 17% y 37% de la población tenga obesidad y sobrepeso respectivamente 5 .…”
Section: Introductionunclassified